Residential complexes in the developing architectural environment - Lidin, Konstantin; Belobrykina, Olga; Buinov, Alexei (project baikal, 2026)
The article considers the phenomenon of a residential complex (housing estate) as an integral part of the architectural environment of the city. The architectural environment and the concepts of housing and residential complex are complex multifactorial constructs. In the course of their consideration, both material (skeleton) parameters and flow (energy) and information (socio- psychological) parameters should be taken into account. Based on a survey conducted by the authors among young students, it was concluded that the next generation prefers their own housing in a separate house rather than an apartment in a multi-storey building. We can expect an increase in demand for housing in low-rise residential complexes.
Keywords: housing; housing estate; architecture; urbanism; urban environment